Active search for respiratory symptoms and late diagnosis of tuberculosis - Patrícia Geórgia Oliveira Diniz Pinheiro; Lenilde Duarte de Sá; Pedro Fredemir Palha; Fabiana Barbosa Assumpção de Souza; Jordana de Almeida Nogueira; Tereza Cristina Scatena Villa (Universidade Federal do Ceará, 2012)
The objective was to analyze the discursivity of managers on the active search for respiratory symptoms and the relationship with the late diagnosis of tuberculosis. Qualitative research with empirical data compiled through interviews with 16 matrix supporters, from a ity in the João Pessoa metropolitan area (Paraiba -PB). Analysis as the technique of discourse analysis, following the French method. Results revealed contradictions between the proposed plan of municipal health and the managers' discourse regarding the actions to control tuberculosis; their lack of knowledge regarding the true meaning of active search, which contributed to cause a passive search for new cases; there are no plan actions for the identification of respiratory symptoms. We conclude that the evidence contributes to the late diagnosis and the need to improve the managers´ knowledge to better understand disease control.